Serum Triiodothyronine Level as an Indicator of Inflammation in Patients Undergoing Dialysis (Iranian Journal of Kidney Diseases, 2010)
Introduction. It has been shown that inflammation affects thyroid function. In patients with end-stage renal disease, low plasma triiodothyronine (T3) may be an unsuspected expression of the inflammatory state of these patients. This study evaluated the correlation between T3 and high-sensitivity C-reactive protein (HSCRP) levels in patients on peritoneal dialysis (PD) and hemodialysis.Materials and Methods. This is a cross-sectional study aiming at the correlation between T3 and HSCRP levels among 30 patients on PD, 30 patients on hemodialysis, and 20 healthy individuals. Serum levels of HSCRP, T3, thyroxine (T4), thyroid stimulating hormone, T3 resin uptake, and free T3 index (FT3I) and free T4 index (FT4I) were compared between the three groups.Results. There were no significant differences between hemodialysis and PD patients in respect to T3, T4, FT3I, and FT4I. In PD and hemodialysis patients, T3 and FT3I were lower than in controls (P < .001), but there was no significant difference between PD and hemodialysis patients. T3 resin uptake and thyroid stimulating hormone differed significantly between PD and hemodialysis patients. There was a significant inverse correlation between HSCRP and T3 and FT3I among hemodialysis patients (P = .04); however, there was no such correlations in PD patients.Conclusions. The relationship between T3 and HSCRP suggests that inflammation might be involved in the low T3 syndrome in hemodialysis patients, but we did not find a significant correlation between T3 and HSCRP levels in patients on peritoneal dialysis.